RANCANG BANGUN TURBIN ANGIN SUMBU VERTIKAL TIPE SAVONIUS DENGAN KETERBATASAN AREA YANG ADA DI GEDUNG PERKULIAHAN TEKNIK ELEKTRO UNIVERSITAS UDAYANA - Rizal Arifin, Ahmad; Indra Partha, Cok Gede; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 11 No 2 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i02.p4, 2024)
The concept of electrical vitality includes the persistent utilize of vitality in standard of living. Renewable vitality that can be changed over into electrical vitality is wind vitality utilizing PLTB. The transformation of wind energy from motor vitality to electrical vitality is the most work of a PLTB framework, with a wind turbine as the most component. The Savonius windmill, for case, is able of working at lower wind speeds, such as those in Indonesia. The aim of this research is to design a Savonius Turbine PLTB with turbine dimensions of 50cm diameter, 50cm height, 25cm blade diameter, and 3 blades. The test results show that the lowest turbine speed is 78 rpm and the highest is 111.5 rpm before the generator is loaded at wind speeds of 3 m/s and 5 m/s. After the generator is loaded with a resistance of 5 W, the lowest turbine speed is 39.5 rpm and the highest is 95.5 rpm at wind speeds of 3 m/s and 5 m/s. The highest turbine efficiency is 10.27%. The lowest torque was 0.07 Nm, and the highest was 0.28 Nm at wind speeds of 3 m/s and 5 m/s.